Methodology of project evaluation : a comparative analysis of OECD manual and UNIDO guidelines - Kannan, K. P. (Kappadath Parameswara), 1949- (Working paper (Centre for Development Studies (Trivandrum, India)), 1975)
Cost-benefit analysis with reference to economic development projects in developing countries.